Transfer Dana Beda Bank Melalui Aplikasi Flip : Studi Perbandingan Hukum Ekonomi Syariah dan Hukum Positif - Faizah, Faizah; Jumailah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
One of the emerging financial technology start-ups in the field of fund transfers is Flip. Flip has created innovations in the field of fund transfers in the form of fund transfer applications without administration fees. The purpose of this study is to discuss fund transfer transactions between different banks through the Flip application and provide an explanation of its provisions between Sharia Economic Law and Positive Law. The research method uses normative juridical with a qualitative approach, regulations, and context. Data collection in the form of documents related to fund transfers between other banks without administration fees through Flip and participant observation, namely, direct observation on the Flip application. The results of the study indicate that the implementation of Financial Technology in Fund Transfer Transactions Between Banks Through the Flip Application has been implemented appropriately by the terms and conditions in the wakalah agreement. According to positive law, fund transfer transactions between other banks through Flip are not yet fully under the Bank Indonesia Regulation on the Implementation of Financial Technology. This study contributes to improving law enforcement in the implementation of fund transfers between banks, especially through the Flip application.